Protein, Calcium, Vitamin D Intake and 25(OH)D Status in Normal Weight, Overweight, and Obese Older Adults: A Systematic Review and Meta-Analysis - Dewansingh, Priya; Reckman, Gerlof A. R.; Mijlius, Caspar F.; Krijnen, Wim P.; van der Schans, Cees P.; Jager-Wittenaar, Harriët; van den Heuvel, Ellen G. H. M. (Frontiers in Nutrition, 2021)
The ageing process is often accompanied by increase in body weight. Older adults with overweight or obesity might have an overconsumption in energy that is accompanied by inadequate intake of protein, vitamin D, and calcium. It is unclear if intake of protein and vitamin D and calcium is sufficient in older adults with overweight/obesity, and whether it differs from older adults with normal weight, since a recent overview of the literature review is lacking. Therefore, we systematically analyzed the current evidence on differences in nutrient intake/status of protein, vitamin D and calcium between older adults with different body mass index (BMI) categories. Randomized controlled trials and prospective cohort studies were identified from PubMed and EMBASE. Studies reporting nutrient intake/status in older adults aged ≥50 years with overweight/obesity and studies comparing between overweight/obesity and normal weight were included. Nutrient intake/status baseline values were reviewed and when possible calculated for one BMI category (single-group meta-analysis), or compared between BMI categories (meta-analysis). Nutrient intake/status was compared with international recommendations. Mean protein (N=8) and calcium intake (N=5) was 0.98 gram/kilogram body weight/day (g/kg/d) [95% Confidence Interval (CI) 0.89-1.08] and 965 mg [95% CI: 704-1225] in overweight/obese. Vitamin D intake was insufficient in all BMI categories (N=5). The pooled mean for vitamin D intake was 6 micrograms [95% CI 4-9]. For 25(OH)D, the pooled mean was 54 nmol/L [95% CI 45-62], 52 nmol/L [95% CI 46-58], and 48 nmol/l [95% CI 33-62] in normal (N=7), combined overweight and obese (N=12), and obese older adults (N=4), respectively. In conclusion, older adults with overweight and obesity have a borderline sufficient protein and sufficient calcium intake, but insufficient vitamin D intake. The 25(OH)D concentration is deficient for the obese older adults.